2010
DOI: 10.1007/s11357-010-9180-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bone resorption by intake of phytoestrogens in postmenopausal women: a meta-analysis

Abstract: Phytoestrogens as selective estrogen receptor modulators like compounds may consider as a therapeutic option in osteoporosis. In this regard, the effect of phytoestrogens on bone biomarkers was examined in several trials which their results are controversial. We aimed this meta-analysis to evaluate the net effect of phytoestrogens on bone markers. A thorough search was conducted from 2000 to 2010 in English articles. All randomized clinical trials were reviewed, and finally, 11 eligible randomized clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Other mechanisms include the influence on calcium absorption and its urinary excretion, prostaglandin synthesis, osteoblast formation and lipid oxidation. The beneficial effect of phytoestrogens on bone resorption markers, and BMD in postmenopausal women in some meta-analysis of randomized controlled trials was reported, in contrast to others [ 112 115 ]. The effect of isoflavones on fracture risk was not seen.…”
Section: Introductionmentioning
confidence: 83%
“…Other mechanisms include the influence on calcium absorption and its urinary excretion, prostaglandin synthesis, osteoblast formation and lipid oxidation. The beneficial effect of phytoestrogens on bone resorption markers, and BMD in postmenopausal women in some meta-analysis of randomized controlled trials was reported, in contrast to others [ 112 115 ]. The effect of isoflavones on fracture risk was not seen.…”
Section: Introductionmentioning
confidence: 83%
“…Phytoestrogens have several potential applications in different diseases. Phytoestrogens decrease bone resorption and delay the progression of osteoporosis in Post-MW [13], exert anti-androgenic effects which could be useful in benign prostatic hypertrophy [14], and may have protective effects in prostate and breast cancers [15], and neuroprotective effects that could improve cognitive functions of the brain [16]. Phytoestrogens also showed a potential to improve CV function and to decrease the risk of CVD associated with menopause [17].…”
Section: Introductionmentioning
confidence: 99%
“…The fasting morning blood samples were collected for quantification of serum β -CTx levels to avoid being confounded by circadian variation and food intake [ 52 ]. It is not surprising that serum β -CTx in this case considerably decreased from baseline after an eight-week isoflavone intervention as other studies have shown that isoflavones can significantly decrease various bone resorption markers (i.e., CTx, pyridinoline, and deoxypyridinoline) [ 47 49 , 53 ]. In fact, this desirable effect may be observed in as early as three weeks following the intervention [ 47 ].…”
Section: Discussionmentioning
confidence: 63%
“…It is not surprising that serum β -CTx in this case considerably decreased from baseline after an eight-week isoflavone intervention as other studies have shown that isoflavones can significantly decrease various bone resorption markers (i.e., CTx, pyridinoline, and deoxypyridinoline) [ 47 49 , 53 ]. In fact, this desirable effect may be observed in as early as three weeks following the intervention [ 47 ]. It is possible that a decline in serum β -CTx such as that found in this study might be able to predict subsequent improvement in the lumbar spine or femoral bone mineral density (if patient continues taking isoflavone capsules for one or two years) [ 51 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation